Evaluation of the Fecal Bacterial Communities of Angus Steers With Divergent Feed Efficiencies Across the Lifespan From Weaning to Slaughter - Welch, Christina B.; Lourenco, Jeferson M.; Krause, Taylor R.; Seidel, Darren S.; Fluharty, Francis L.; Pringle, T. Dean; Callaway, Todd R. (Frontiers in Veterinary Science, 2021)
Numerous studies have examined the link between the presence of specific gastrointestinal bacteria and the feed efficiency of cattle. However, cattle undergo dietary changes during their productive life which can cause fluctuations in their microbial consortium. The objective of the present study was to assess changes in the fecal microbiome of beef steers genetically selected to be divergent in feedlot feed efficiency, to determine whether differences in their fecal microbiomes could be detected as early as weaning, and continued throughout the rearing process regardless of dietary changes. Fecal samples were collected at weaning, yearling age, and slaughter for a group of 63 steers. Based on their feedlot-finishing performance, the steers were selected and divided into two groups according to their residual feed intake (RFI): efficient steers (low-RFI; n=7) and inefficient steers (high-RFI; n=8). To ascertain the fecal microbial consortium and volatile fatty acid (VFA) content, 16S rRNA gene sequencing and VFA analysis were performed. Overall, bacterial evenness and diversity were greater at weaning compared to yearling and slaughter for both efficiency groups (P < 0.001). Feedlot RFI linearly decreased as both Shannon diversity and Ruminococcaceae abundance increased (R2 = 65.6% and 60.7%, respectively). Abundances of Ruminococcaceae, Rikenellaceae, and Christensenellaceae were higher at weaning versus yearling age and slaughter (P < 0.001); moreover, these families were consistently more abundant in the feces of the low-RFI steers (for most of the timepoints evaluated; P ≤ 0.05), compared to the high-RFI steers. Conversely, abundances of Bifidobacteriaceae were numerically higher in the feces of the low-RFI steers throughout their lifespan. Total volatile fatty acid concentrations increased at slaughter compared to weaning and yearling for both efficiency groups (P < 0.001). The acetate:propionate ratio decreased linearly (P < 0.001) throughout the life of the steers regardless of their efficiency, reflective of dietary changes. Our results indicate that despite fluctuations due to animal age and dietary changes, specific bacterial families may be correlated with feed efficiency of steers. Furthermore, such differences may be identifiable at earlier stages of the production cycle, potentially as early as weaning.